Study of Traditional Uses of Medicinal Shrubs in Begnas-Rupa Lake Area - Dwa, Om Prasad (Himalayan Biodiversity, 2019)
The present paper is based on the work done about traditional uses of medicinal shrubs in Begnas-Rupa lake area from Oct 2018 to Apr 2019. This result was based on survey carried out consulting participatory techniques to collect information about collection and utilization of such plants on that area. Important information and other details about the respective plants were collected by discussion with native inhalers and traditional medicine practitioners. The result revealed that 20 Species of medicinal shrubs belonging to 17 families have been locally used Included families are Acanthaceae, Apocynaceae, Asclepidaceae, Asteraceae, Berberidaceae, Capparidaceae, Euphorbiaceae, Leguminosae, Loganiaceae, Lythraceae, Malvaceae, Melastomataceae, Oleaceae, Polygonaceae, Primulaceae, Rhamnaceae and Rutaceae.